Maternal Interaction Relates to Neural Processing of Self‐Related Multisensory Information in 5‐Month‐Olds - Kollakowski, Nina‐Alisa; Pletti, Carolina; Paulus, Markus (Developmental science, 2025)
ABSTRACT The ontogenetic origin of the self in infancy is a topic of ongoing debate. Although influential developmental and neurocognitive theories propose that caregiver‐infant interactions play an important role in infants’ self‐development, little is known about the specific mechanisms involved. Some theories highlight the importance of caregiver sensitivity and touch, while others propose that caregiver contingency plays a central role. The study aimed to investigate infants’ self‐perception by measuring brain activation in the posterior superior temporal sulcus (pSTS), a region previously associated with self‐related processing. A total of 118 mother‐infant dyads participated in a free‐play interaction, during which maternal sensitivity and touch were measured. Additionally, a face‐to‐face interaction was conducted to measure maternal contingency. Infants' brain activation was measured using functional near‐infrared spectroscopy (fNIRS). They watched a video of their own face while being stroked by a brush on the cheek. The video was either live and the stroking was synchronous to the video (contingent) or the video was delayed by 3 s, which made the stroking asynchronous (non‐contingent). The results showed that infants exhibited more HbO‐activation in the right pSTS in the non‐contingent condition. Importantly, the more sensitive the mothers were and the more they touched infants during free play, the less differential activation the infants showed in response to both conditions. This effect was driven by infants showing less activation to the non‐contingent condition when their mothers exhibited more care, maybe because of a smaller prediction error for non‐contingent self‐related multisensory information. Overall, the study deepens our knowledge of how early social interactions relate to the emergence of the self in infancy.